A Path Analysis of Physical Activity Intensity and Waist Circumference on the Lipid Profile: A Cross-sectional Study of NHANES Data. Issue 5 (2nd September 2020) - Greiner, Benjamin; Ottwell, Ryan; Nicks, Savannah; Lee, Abraham; Hartwell, Micah
ABSTRACT: Background: Physical activity is widely known to positively affect serum lipids. Yet, no study has utilized a path analysis methodology, which is more efficacious at analyzing complex relationships than simple regressions, to incorporate the cumulative effects of physical activity and waist circumference on lipids. Purpose: Our objective was to analyze the effects of moderate and vigorous physical activity, combined with waist circumference and sex, on serum lipids. Methods: A cross-sectional analysis of US male and female adults from 2011 to 2016 NHANES data was collected. Path analyses for each lipid value included physical activity (moderate and vigorous in MET per minute), waist circumference (per cm), and sex and were performed using R 3.6.1. Results: Our sample size was 16, 221 (N = 225, 364, 595). Vigorous intensity exercise was associated with decreased high-density lipoproteins (HDL) and triglycerides (TG), while indirectly influencing total cholesterol, low-density lipoproteins, HDL and TG through decreased waist circumference. Moderate physical activity had no statistically significant impact on lipids or waist circumference. Discussion: Vigorous physical activity positively affects dyslipidemia when combining sex and decreasing waist circumference. This impact was not present when moderate physical activity was applied. Translation to Health Education Practice: Physicians and Health Educators should encourage patients to perform vigorous physical activity and weight loss to improve lipids.